Emerging environmental, health and safety issues in China: practical impacts on international investors. (1st January 1999) - Anwar, H.
The Chinese government at the highest levels continues to stress the importance of environmental protection. The environmental consequences of rapid industrialisation and a burgeoning population are now unavoidable to citizens and government ministers alike. Among the major challenges for environmental protection and health and safety regulations in China are improving the transparency of government bodies and statistics, encouraging horizontal and vertical coordination on regulation and projects between and within ministries, ensuring economic viability of both municipal and commercial sector environmental protection projects, and enforcing ever-strengthening regulations. Government officials at all levels will no doubt feel pressure to advance new legislation while maintaining a high level of GDP growth, which invariably will place a priority on development and not on environmental, health and safety issues. Given the increasingly precarious economic conditions and ongoing reform of state-owned enterprises, it may be difficult for the Chinese government to follow through on high-minded efforts. This paper discusses the changing regulatory framework, likely enforcement inequities and implications for multinationals seeking to comply.